Quantitative easing, the repo market, and the term structure of interest rates - Ruggero Jappelli; Loriana Pelizzon; Marti G. Subrahmanyam (Leibniz Institute for Financial Research SAFE, 2023)
We develop a quantity-driven general equilibrium model that integrates the term structure of interest rates with the repurchase agreements (repo) market to shed light on the combined effects of quantitative easing (QE) on the bond and money markets. We characterize in closed form the endogenous dynamic interaction between bond prices and repo rates, and show (i) that repo specialness dampens the impact of any given quantity of asset purchases due to QE on the slope of the term structure and (ii) that bond scarcity resulting from QE increases repo specialness, thus strengthening the local supply channel of QE.
Keywords: E43; E52; G12; 330; Term Structure of Interest Rates; Repo Specialness; Money Market; Quantitative Easing